2002
DOI: 10.1073/pnas.082011999
|View full text |Cite
|
Sign up to set email alerts
|

Functional correction of established central nervous system deficits in an animal model of lysosomal storage disease with feline immunodeficiency virus-based vectors

Abstract: Gene transfer vectors based on lentiviruses can transduce terminally differentiated cells in the brain; however, their ability to reverse established behavioral deficits in animal models of neurodegeneration has not previously been tested. When recombinant feline immunodeficiency virus (FIV)-based vectors expressing ␤-glucuronidase were unilaterally injected into the striatum of adult ␤-glucuronidase deficient [mucopolysaccharidosis type VII (MPS VII)] mice, an animal model of lysosomal storage disease, there … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
84
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(86 citation statements)
references
References 42 publications
2
84
0
Order By: Relevance
“…Although this can be achieved under certain circumstances in the mouse brain, it is a much more difficult problem in a large brain. [3][4][5][6][7][8][9] The brain of a child in the first year of life, when disease diagnosis is most likely and treatment is expected to be most effective, is 1000-2000 times larger than the mouse brain. To provide a foundation for initiating human gene therapy trials, gene transfer to large regions of the brain will need to be demonstrated in a large animal model.…”
Section: Introductionmentioning
confidence: 99%
“…Although this can be achieved under certain circumstances in the mouse brain, it is a much more difficult problem in a large brain. [3][4][5][6][7][8][9] The brain of a child in the first year of life, when disease diagnosis is most likely and treatment is expected to be most effective, is 1000-2000 times larger than the mouse brain. To provide a foundation for initiating human gene therapy trials, gene transfer to large regions of the brain will need to be demonstrated in a large animal model.…”
Section: Introductionmentioning
confidence: 99%
“…Exceptional results in the central nervous system have been obtained [47]. Although controlled infectivity and efficacy comparisons on a per particle basis have been lacking, in several systems, FIV vectors have produced excellent levels of gene transfer and expression in cultured human organs [45,55,56].…”
Section: Introductionmentioning
confidence: 99%
“…FIV vectors have been used to target cells in the brain, eye, airway, hematopoietic system, liver, muscle and pancreas [8,15,16,19,[45][46][47][48][49][50][51][52][53][54][55][56][57]. Exceptional results in the central nervous system have been obtained [47].…”
Section: Introductionmentioning
confidence: 99%
“…Low inflammatory and immunogenic characteristics along with minimal toxicity and superior infectivity for terminally differentiated cells render lentiviral vectors especially suitable for delivery of genes into neurons, while their intrinsic capability of integrating transgenes into the genome of host cells with minimal risks for the activation of protooncogenes ensures long-term expression of the genes of interest-a critical condition for treatment of chronic conditions such as AD [3,58]. Despite the fact that lentiviruses belong to the superfamily of enveloped virions (which include a variety of retroviruses, alphavirus, and herpes simplex virus, with superb intra-axonal mobility) characterized by a long transduction range, the VSV-G pseudotyped vectors used in the present study were shown to exhibit limited intra-axonal mobility [59,60]. The latter is in agreement with scant labeling of ependymal cells and few scattered GFP-positive cells of the lateral septum and caudate nucleus after intraventricular injection of GFP-encoding lentiviral vectors.…”
Section: Discussionmentioning
confidence: 82%